Pengaruh Frekuensi Perdagangan, Volume Perdagangan, Trading Day, dan Volatilitas Pasar terhadap Return Saham Perusahaan Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2020–2024 - Nadiya Sasmita Sari; Sintia Safrianti; Janusi Waliamin (Lembaga Yasin AlSys, 2025)
The stock market is a dynamic investment instrument where various micro-market factors influence stock price movements and the returns received by investors. This study aims to analyze the effect of trading frequency, trading volume, trading day, and market volatility on the stock returns of consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative approach was employed, with the population comprising all consumer goods sector companies on the IDX and a purposive sample of 41 companies. Data were obtained from annual financial reports and analyzed using classical assumption tests, multiple linear regression, and hypothesis testing with SPSS software. The results indicate that trading frequency and market volatility significantly affect stock returns, while trading volume and trading day do not have a significant impact. These findings confirm that trading frequency and volatility are critical indicators for stock investment decision-making. The implication is that investors and capital market players should consider these variables to develop more accurate and responsive investment strategies aligned with market dynamics.